Family involvement, family member composition and firm innovation - Qingmei Tan; Zixuan Liu; Peixuan Geng (China Journal of Accounting Research, 2020)
Based on the data of Chinese listed family firms from 2008 to 2016, we investigate the impact of family involvement on firm innovation and the moderating effect of family member composition. The results show that increased family involvement significantly reduces R&D investment intensity and the number of patent applications. With the increased richness of the kinship of family members involved in management, the negative impact of family involvement on patent applications is weakened, but family member composition does not have a significant moderating effect on the relationship between family involvement and R&D investment intensity. Further analysis shows that the number of invention patent applications decreases as the degree of family involvement increases, but family involvement has no significant effect on utility model patent and design patent applications. Family member composition has a significant moderating effect on the relationship between family involvement and invention patent applications. The results have value as a reference for exploring how family involvement affects firm innovation and can also help the actual controller to take effective measures to optimize family member composition and improve the innovation performance of family firms.
Keywords: 650; Family firms; Family involvement; Family member composition; R&D investment; Patent applications